2022
DOI: 10.3389/fenrg.2022.827794
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations of Carbon Dioxide Storage in Selected Geological Structures in North-Western Poland

Abstract: In this study, dynamic simulation models of CO2 injection into saline aquifers of the Choszczno-Suliszewo structure located in north-western Poland were constructed for two scenarios with different injection rates. The injection rates of 1 Mt CO2/year and 2 Mt CO2/year were analysed for each of the injection wells. Changes in pressures, characteristic for the sequestration process, were analysed; in addition, the spatial distribution of free CO2 saturation in the structure and carbon dioxide dissolved in brine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Two additional emitters expected to be built in the future were also taken into account in the scenario: CCGT New Rybnik (800 MW) and IGCC Łaziska (250 MW). The possibility of CO 2 sequestration in geological formations in the region of Upper Silesia in Poland have been investigated by several authors [26][27][28][29][30][31]. Based on these studies, four possible CO 2 storage sites have been identified, with a total estimated capacity of 111.5 Mt (Table 2).…”
Section: Identification and Characteristics Of The Main Co 2 Emitters...mentioning
confidence: 99%
See 2 more Smart Citations
“…Two additional emitters expected to be built in the future were also taken into account in the scenario: CCGT New Rybnik (800 MW) and IGCC Łaziska (250 MW). The possibility of CO 2 sequestration in geological formations in the region of Upper Silesia in Poland have been investigated by several authors [26][27][28][29][30][31]. Based on these studies, four possible CO 2 storage sites have been identified, with a total estimated capacity of 111.5 Mt (Table 2).…”
Section: Identification and Characteristics Of The Main Co 2 Emitters...mentioning
confidence: 99%
“…Based on these studies, four possible CO 2 storage sites have been identified, with a total estimated capacity of 111.5 Mt (Table 2). The possibility of CO2 sequestration in geological formations in the region of Upper Silesia in Poland have been investigated by several authors [26][27][28][29][30][31]. Based on these studies, four possible CO2 storage sites have been identified, with a total estimated capacity of 111.5 Mt (Table 2).…”
Section: Identification and Characteristics Of The Main Co 2 Emitters...mentioning
confidence: 99%
See 1 more Smart Citation
“…The process of decarbonisation of the energy sector in Poland will be long and difficult considering the economic as well as social aspects (Tokarski et al 2021). The application of coal gasification technologies in the Polish energy sector may successfully contribute to facilitate this process (Cabuk et al 2020;Smolinski et al 2021;Park et al 2020) while combined with the CCUS (Urych et al 2022;Zdeb et al 2019;Van Bergen et al 2009;). Bielowicz (2019) presents the deep analysis of the Polish lignite for gasification in the CO 2 atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, blue hydrogen is produced by steam reforming of natural gas (Van Dyk et al 2009;Verhelst et al 2011; Polish Hydrogen Strategy to 2030 with the 2040 perspective). Another option of hydrogen production in the midterm of hydrogen economy development is associated with the construction of coal gasification systems which, however, due to their high emission (above 10 kg CO 2 eq/1 kg H 2 ), must be combined with the CCS/ CCUS technologies (Krawczyk et al 2016;Urych et al 2022).…”
Section: Introductionmentioning
confidence: 99%